Estimation of selected heavy metals and bacteria in sludge of wastewater treatment unit at AL-Nassiryia city southern of Iraq - Basim Y. Alkhafaji; Nooraldeen S. Alseedi; Saad S. Hamim (University of Thi-Qar Journal of Science, 2019)
The present study was concerned to estimation the concentrations of the selected heavy metals (Zinc, Copper, Lead, Nickel and Cadmium) in the sewage sludge, which was collecting  from the wastewater treatment unit from  the center of Al-Nassiriya city during the seasons of the year ( autumn , winter , spring and summer) from October, 2016 to August, 2017. Three stations were chosen to execute this study, station (1): represent the pre-treatment; station (2): represent post-treatment and station (3)  represent after dumping in the river. The results of the present study showed a high concentration of heavy metals in dry sludge was Zinc (91.86) µg/g dry wt. in the (st.1) in Spring season, while the Nickel (5.19) µg/g dry wt. at the (st.1) in Summer. The high concentration of copper (41.20) µg/g dry wt. at the ( st.3) in Winter , and lead was (50.17) µg/g dry wt. at the (st.3) in Winter, and cadmium was (97.20) µg/g dry wt. at (st.2) in Winter. The high concentrations of fecal coliforms was (18000) cells /100 ml at (st.1) in winter, while the high number of total coliforms was (160000) cells/100 ml at (st.1) in winter. According to statistical analysis; The results of the present study showed a significant differences between the concentrations of heavy metals during the seasons of the year at the stations, as well as significant differences between the bacteria at the stations that were studied.